Wined and died in New Orleans - Byron, Ellen (Byron, Ellen. Vintage cookbook mystery ;, 2023)
When a dead body turns up in the magnificent Bon Vee Culinary House Museum in New Orleans, the NOPD zeroes in on the head of the Charbonnet family, known for their valuable French wine, as Ricki James-Diaz wonders what kind of secret her mentor has bottled up.